Analisis Faktor Penghambat Kesehatan Koperasi Produsen Aneka Sulaman di Kabupaten Agam - Menik Kurnia Siwi; Tri Kurniawati; Jean Elikal Marna (Jurnal Ecogen, 2020)
This activity aims to describe the inhibiting factors of the health of Aneka Sulam Producer's Cooperative in Agam Regency. Cooperative health level based on seven aspects such as capital, productive asset quality, management, efficiency, liquidity, independence and growth, identity of the cooperative, and analyzing the factors that influence it. The results of the activities showed that the factors that hampered the health of cooperatives included internal disputes that were expected to cause difficulties in the development of the cooperatives concerned, the wrong of bookkeeping or window dressing so that the impact on the assessment became erroneous and the cooperatives carried out savings and loan business activities but were not recorded correctly. For this reason, it is necessary to have better cooperative management in the future.Keywords : cooperative health, capital, management, liquidity, identity of the cooperative